The Effect Of Payment Ease, Complete Product Information, And Free Shipping Vouchers On Purchase Decisions On The E-Commerce Website Tokopedia (A Case Study Of The Community Of Jalan Garu III, Harjosari I, Medan Amplas) - Zamzami Zamzami; Anggia Sari Lubis; Toni Hidayat; Rukmini Rukmini; Horia Siregar (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
TThe development of the internet has driven changes in people's shopping behavior from offline to online, thus increasing the growth of e-commerce in Indonesia. This study aims to determine the effect of Ease of Payment, Completeness of Product Information, and Free Shipping Vouchers on Purchasing Decisions in Tokopedia e-commerce. The study used a quantitative approach with a sample of 97 respondents from Jalan Garu III Harjosari I Medan Amplas who were selected using probability sampling techniques with the Slovin formula. Data analysis used multiple linear regression through SPSS 25.0. The results showed that simultaneously the three variables had a significant effect on Purchasing Decisions with an Fcount of 46.587 > Ftable 2.70. Partially, Ease of Payment (tcount 5.479), Completeness of Product Information (tcount 3.019), and Free Shipping Vouchers (tcount 4.688) also had a significant effect because all tcount values ​​were > ttable 1.661. The coefficient of determination (R²) value of 0.775 shows that the three variables are able to explain 77.5% of the Purchasing Decision, while the remaining 22.5% is influenced by other factors outside the research.